Skin Diseases of the Dog and Cat, Third Edition - Nuttall, Tim; Eisenschenk, Melissa; Heinrich, Nicole A.; Harvey, Richard G.; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
A Colour Handbook of Skin Diseases of the Dog and Cat was one of the first books to bring key information about skin diseases to clinicians in an easy-to-use problem-oriented format. This fully revised and updated Third Edition responds to the huge growth in knowledge about skin conditions over the last decade, including the discovery of new conditions, the development of new approaches to management, and effective new treatment options.13 chapters covering over 120 skin, claw and ear conditions classified by their principle presenting sign.Concise, systematically structured text covering definition, aetiology and pathogenesis, clinical features, differential diagnoses, diagnostic tests and management.Flow charts in each chapter to help clinicians get to the right diagnosis.Special focus on diseases affecting paediatric patients as well as chapters discussing paw, ear and nasal planum diseases. Explanation of new treatments for atopic dermatitis.Over 350 superb colour photographs and diagrams, mostly new for this this edition.A focus on clinical practice and the need to explain the disease to the owner.Up-to-date and fully referenced throughout.This practical book continues to provide an entirely comprehensive guide to the diagnosis and management of veterinary skin conditions, in a format that is easily accessible for busy clinicians.
Chapter 1 Basics. Chapter 2 Pruritic Dermatoses. Chapter 3 Papular, pustular, and/or crusting diseases. Chapter 4 Alopecic dermatoses. Chapter 5 Diseases of abnormal keratinization and scaling. Chapter 6 Ulcerative Dermatoses. Chapter 7 Diseases with draining tracts or sinus formation. Chapter 8 Diseases of the paws and nails. Chapter 9 Diseases of the nasal planum. Chapter 10 Pediatric and congenital disease. Chapter 11 Nodular diseases and neoplasia. Chapter 12 Diseases of abnormal pigmentation. Chapter 13 Diseases of the ears--. -- --
Includes bibliographical references and index.
Also available in print format.
Keywords: Dermatoses; Environmental Dermatoses; Focal Alopecia; Hormone-related Dermatoses; Nail Disorders; Nodular Dermatoses; Otitus Externa; Papular Dermatoses; Pigmentary Abnormalities; Pruritic Dermatoses; Pustular Dermatoses; Ulcerative Dermatoses; Dogs -- Diseases; Cats -- Diseases; Veterinary dermatology; Skin Diseases -- veterinary; Dog Diseases; Cat Diseases; Electronic books